KORELASI KETERAMPILAN MEMBACA PEMAHAMAN TEKS EKSPOSISI DENGAN KETERAMPILAN MENULIS TEKS EKSPOSISI SISWA KELAS X SMA NEGERI 7 PADANG - M. Hafrison, Novia, Tressyalina, (Universitas Negeri Padang, 2017)
The purpose of this study is to analisis correlation between comprehension reading skill of exposition text and writing skill of text exposition for students at class X SMAN 7 Padang. The type of this stud was quantitative research with descriptive method and correlation design. Population in this study was students at class X SMAN 7 Padang that enrolled in year of school 2016/2017. Sample in study was determined by application of random sampling technique. Based on study finding, it was concluded that there was a significant correlation between comprehension reading skill of exposition text and writing skill of text exposition for students at class X SMAN 7 Padang with deliberate degree n-1 and confident level of 95%; tcount > ttable (3.58 > 1.68). Therefore, writing skill of text exposition has a correlation with comprehension reading skill of exposition text or student need to comprehend the exposition text to write it.Kata kunci: korelasi, membaca pemahaman, menulis, teks eksposisi